Design of low complexity variable digital filters and filter banks for software defined radio receivers - Ambede, Abhishek (2016)
To seamlessly support the existing and upcoming wireless communication standards, the software defined radio (SDR) has been proposed as a solution. SDRs can process signals of different wireless communication standards by software reconfiguration of the same transceiver architecture, thereby reducing hardware resource utilization and associated costs. To perform multi-standard channelization, i.e., extraction of desired radio channels (frequency bands) from a wideband input signal, SDR receivers typically employ variable digital filters (VDFs) and filter banks that provide variable frequency responses by controlling a small set of parameters. VDFs and filter banks are also used in SDR based cognitive radios (CRs) to perform spectrum sensing (detection of presence/ absence of licensed user signals in a wideband input frequency range) for dynamic spectrum access, to achieve opportunistic and efficient usage of the radio frequency spectrum. Realizing such VDFs and filter banks which showcase the desired attributes of high frequency response flexibility and low implementation complexity is a challenging task. To address this challenge, new algorithms and various architectures for designing VDFs and filter banks have been proposed in this thesis. The first work presents design techniques to obtain variable frequency responses using the same set of prototype filter coefficients, along with the corresponding mathematical formulations. Two techniques are proposed – a modified coefficient decimation method (MCDM) and the improved coefficient decimation method (ICDM), the latter being a combination of the proposed MCDM and the conventional coefficient decimation method (CDM). Both the proposed techniques, i.e., MCDM and ICDM, involve selective usage of filter coefficients by performing operations such as replacing them by zeros and retaining/ discarding them appropriately to obtain variable frequency responses. The ICDM is categorized into ICDM-I and ICDM-II, each comprising of two distinct coefficient decimation operations. The ICDM provides discrete control over the bandwidths and center frequencies of the subbands in the obtained frequency responses. The second work presents the design of VDFs which can be used for channelization in SDR receivers. Three such VDFs, one each based on ICDM-I, ICDM-II and comprehensive ICDM are proposed and analysed. The comprehensive ICDM based VDF involves both ICDM-I and ICDM-II operations and features their constituent advantages while minimizing the effects of their individual limitations. The comprehensive ICDM based VDF can provide variable lowpass, highpass, bandpass, bandstop and multi-band frequency responses on-the-fly, by performing appropriate ICDM operations on the same set of prototype filter coefficients. Similar to the design of VDFs based on ICDM-I, ICDM-II and comprehensive ICDM, the third work presents design of filter banks based on these three techniques. While the ICDM-I based filter bank can only be used for uniform channelization, the ICDM-II and comprehensive ICDM based filter banks can be used in SDR receivers for uniform as well as non-uniform channelization of signals corresponding to multiple wireless communication standards. The fourth work presents the design of VDFs based on the combination of all pass transformation (APT) technique and the proposed ICDM. The proposed VDFs employ 1st order APT techniques along with the ICDM to provide variable lowpass, highpass, bandpass, bandstop frequency responses with unabridged control over the bandwidths and center frequencies of the constituent subbands. A spectrum sensing scheme employing VDFs based on the combination of APT and ICDM is proposed. Also, pipelined hardware implementation architectures for realizing high speed APT based VDFs are presented. These VDFs based on the combination of APT and ICDM can be used for realizing low complexity spectrum sensing schemes in SDR based CR receivers, wherein unabridged control over cutoff frequency is desired to obtain a fine sensing resolution over the entire Nyquist frequency range.